The Sacred Phenomenology of Mount Kawi Cemetery in Malang: Examining Its Connection to the Manuscript Serat Iman Sujana Found at Gunung Kawi - Nur Awalin, Faturrohman; Mulyana; Afendy Widayat (Center for Research and Development of Religious Literature and Heritage, 2025)
The sacredness of Gunung Kawi Malang is deeply associated with the figures of Kiai Zakaria II (Eyang Djoego) and R.M Iman Sujana. This study examines the phenomenology of sacredness at Gunung Kawi Malang, focusing on its conceptual underpinnings and implications. Central to this inquiry is the Serat Iman Sujana manuscript, discovered at Gunung Kawi Malang, which provides key insights into the sacredness attributed to the site. Employing a phenomenological approach, this research interprets the layers of sacred meaning embedded in Gunung Kawi Malang, particularly in light of its historical role as a center for mystical practices, including pesugihan rituals. Additionally, a literature study of the Serat Iman Sujana manuscript was conducted to deepen the analysis. Findings reveal that the sacralization of Gunung Kawi Malang is significantly influenced by Kiai Zakaria II (Eyang Djoego) and R.M Iman Sujana. The connection between these figures and the Serat Iman Sujana manuscript is reflected in the presence of Raden Iman Sujana as a key character, whereas Kiai Zakaria II is notably absent from the text. The manuscript portrays Iman Sujana as a waliyullah (Allah representative), tracing his lineage back to the apostle of Allah. If, as the Kekancingan letter suggests, Iman Sujana was the great-grandfather of Hamengkubuwana I, then the sanctification of Gunung Kawi Malang through these figures aligns with the broader tradition of Islamic scholarship. Additionally, oral traditions depict Iman Sujana not only as a spiritual scholar but also as a soldier and mentor to Pangeran Diponegoro, further reinforcing his multifaceted role in both religious and historical narratives.